Representasi Warna Ungu dalam Novel The Color Purple Karya Alice Walker: Analisis Semiotika - Nessa Aqila Anggraini (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
This article aims to represent the color purple in Alice Walker's novel The Color Purple. This article uses the semiotic study of Charles Sanders Pierce. The process of meaning according to Pierce is divided into three stages, namely the absorption of the signifier (representament), the appointment of the representamen on the object and the interpretation of the further (interpretant). This paper also uses a qualitative descriptive approach. The results of the research in this paper indicate that the researcher found a signifier (representament) of the word "Ungu" which refers to objects in the form of pants (icon) and letters (index), as well as woman and God as symbols. At the final interpretation stage in the novel which can lead to freedom (rheme) as an interpretant. These signs are scattered in the form of words, phrases, and sentences contained in the novel. Based on the signs that have been collected, it can provide an understanding of the picture of black women's lives that tend to lead to social problems, namely freedom.